Behavioral Analysis of Customer Transaction Patterns in Financial Fraud ‎Detection: An Integrated Machine Learning Approach - Balcıoğlu, Yavuz Selim; Merter, Abdullah Kürşat; Çelik, Beylem; Karakaya, Turhan (International Journal of Basic and Applied Sciences, 2025)
Financial fraud detection has emerged as a critical challenge in the contemporary digital economy, with ‎sophisticated fraudulent schemes continuously evolving to exploit vulnerabilities in financial systems. This study ‎presents a comprehensive behavioral analysis of customer transaction patterns to enhance fraud detection ‎capabilities through an integrated machine learning approach. Utilizing a dataset of 100 financial transactions ‎encompassing diverse transaction types (purchases, transfers, withdrawals), customer profiles, and monetary ‎values, we develop a multi-dimensional framework for identifying fraudulent activities. Our analysis reveals ‎significant variations in fraud likelihood across transaction types, with transfer operations exhibiting the highest risk ‎profile at 55%, while withdrawal transactions demonstrated no fraudulent activity. Furthermore, fraudulent ‎transactions showed monetary values 28% higher than legitimate transactions, indicating distinct behavioral ‎patterns. The study contributes to the literature by integrating behavioral finance theory with anomaly detection ‎techniques, providing both theoretical insights and practical applications for financial institutions. Our findings ‎demonstrate that customer behavioral patterns, transaction types, and monetary thresholds serve as robust ‎predictors of fraudulent activity, with machine learning models achieving accuracy rates exceeding 94% while ‎maintaining low false positive rates. The results have important implications for real-time fraud detection systems ‎and risk management strategies in financial institutions‎.